1996
DOI: 10.1103/physrevlett.76.2448
|View full text |Cite
|
Sign up to set email alerts
|

Resonant X-Ray Emission Spectroscopy of Molecular Oxygen

Abstract: Resonant soft x-ray emission spectroscopy has been applied to study the issue of symmetry breaking upon core-hole excitation in molecular oxygen. The results provide direct evidence that the inversion symmetry is not broken in the core-excited states. Furthermore, the experiments themselves demonstrate a new experimental technique of broad applicability for studies of electronic structure and excitation dynamics in free atoms and molecules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
92
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(102 citation statements)
references
References 30 publications
10
92
0
Order By: Relevance
“…This intrinsic asymmetry with respect to emission into the inner and outer regions of the molecule explains asymmetric electron emission behavior in diatomic homonuclear molecules [12], which was for a long time not understood well, because it was in distinct contrast to results on the same subject obtained by soft x-ray experiments instead of electron emission [13]. Such energy resolved coincidence spectroscopy of intramolecular scattering processes has a great potential for time-dependent studies of dissociating molecular systems.…”
mentioning
confidence: 74%
“…This intrinsic asymmetry with respect to emission into the inner and outer regions of the molecule explains asymmetric electron emission behavior in diatomic homonuclear molecules [12], which was for a long time not understood well, because it was in distinct contrast to results on the same subject obtained by soft x-ray experiments instead of electron emission [13]. Such energy resolved coincidence spectroscopy of intramolecular scattering processes has a great potential for time-dependent studies of dissociating molecular systems.…”
mentioning
confidence: 74%
“…Figure 4 shows the dispersion and the FWHM of the L 3 -N 4,5 emission line in CH 3 I and of the Cl K-L emission line in CH 3 Cl as a function of the incident photon energy detuning from the resonance. The error bars indicated on the graphs in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For example, it was demonstrated that a dynamical symmetry breaking in molecules occurring on the time scale of the core-hole lifetime can be studied due to the symmetry dependence of the x-ray emission intensities on the selection rules. 2,3 Polarization and anisotropy of x-ray emission can be used to study orbital components, bond directions, and molecular orbital symmetries. [4][5][6] Recently, molecular-field effects a) Author to whom correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…For a two-photon process such as XRRS, the dipole selection rule requires that the final-state parity be the same as the initialstate parity. This parity selection rule has been confirmed 67,95,96 in the cases of XRRS spectra of N 2 and O 2 , for which the x-ray wavelengths are ª30 Å and ª23 Å, respectively, i.e., large compared with internuclear distances. Skytt et al 67,97 and Glans et al 96 discuss the case of C O 2 , which also has inversion symmetry.…”
Section: Nondipole X-ray Resonant Raman Scattering From Moleculesmentioning
confidence: 63%